Pemilihan Dosen Terbaik di Multimedia Nusantara Polytechnic dengan Metode Analytical Hierarchy Process (AHP) - Sinta Andriani; Abyan Dzakwan Permana; Mika Medi Ariansyah; Dewi Hajar (Multmedia Nusantara Politeknik, 2026)
The selection of the best lecturer is a form of institutional appreciation for the lecturer's contribution in carrying out the Tri Dharma of Higher Education. At Multimedia Nusantara Polytechnic (MNP), this process is still done manually so it tends to be subjective and inefficient. This study aims to determine the best lecturer using the Analytical Hierarchy Process (AHP) method based on five criteria: Research (C1), PKM (C2), EDOM/Learning (C3), Publication (C4), and IPR (C5). Data were obtained through interviews and documentation from the MNP Research and Collaboration section. The calculation results show that the Publication criterion has the highest priority weight of 0.3953 (39.53%), followed by EDOM 0.2395 (23.95%), Research 0.1730 (17.30%), PKM 0.1194 (11.94%), and IPR 0.0728 (7.28%). Of the 19 lecturers evaluated, lecturer H was ranked first with a final score of 0.1511, followed by lecturer I with a score of 0.0996 and lecturer L with a score of 0.0819. The application of the AHP method has been proven to produce a more systematic and objective ranking compared to manual assessment.